Pengaruh Determinan Tidak Langsung Stunting dengan Kejadian Stunting Balita di Papua New Guinea Tahun 2018: Indirect Determinant Effects of Stunting with Toddler Stunting Incident in Papua New Guinea in 2018 - Khoiriyah, Riza; Mahmudiono, Trias; Nadhiroh, Siti Rahayu (Universitas Airlangga, 2024)
Background: Papua New Guinea has a significant problem with stunting, with a prevalence rate of 46.5% in 2018. Objectives: This study aimed to analyze the effect of various factors on stunting in Papua New Guinea in 2018. These factors include characteristics of the child (gender, age, and ownership of health insurance) and household environmental factors such as the mother's education level, number of toddlers in the household, drinking water sources, and availability of restrooms. Methods: This study employed a cross-sectional research design using secondary data from